Strategi Pengemasan Dan Pemasaran Beras Organik Dan Jamur Tiram Di Dusun Kanten, Desa Kebonagung, Bantul - Yunita, Ani (Universitas Muhammadiyah Yogyakarta, 2018)
Packaging and marketing program of oyster mushroom and rice products is caused by the absence of pack-aging and marketing strategy of oyster mushroom and rice in Kanten, KebonAgung, Imogiri, Bantul, Special Region of Yogyakarta. This program aims to increase productivity, packaging innovation and marketing of organic rice products and oyster mushrooms in the Kanten. Methods of implementation undertaken in this program include sosialization, training and mentoring by Community Service Team. Implementation of this community service has a target that is Sasono Catur Members of Farmers Group and Sekar Arum Members of Women Farmer Group. Materials provided include entrepreneurial materials with emphasis on packaging and online marketing of oyster mushroom and rice products. The results and discuss of this community service in the form of packaging of organic rice products labeled â€œberas sehatâ€ with size 3 and 5 kg and oyster mushroom packaging labeled â€œjamur kanten crispyâ€ that weighs 1-5 ounces. Marketing of organic rice and jamur kanten crispy in this community service is in the form of manual marketing by offering to store/ supermarket and online through shopee account. Keywords: Strategy, Packaging, Marketing, Organic Rice Product, Oyster Mushroom.